Examination of Psychological Ability Levels of Middle School Students Towards Sports (Sample of Konya City) - Abdullah Sencer Temel; Yalçın Tükel; Davut Atılgan (Selcuk University, 2021)
The main purpose of this study, to find out the ability of athlete students who study at the secondary school level to cope with psychological difficulties. The research was carried out in a descriptive screening model. The sample of the study consists of 237 participants, who are athlete student studying in secondary schools within Konya Provincial Directorate of National Education in Konya. Research data were collected on september, october and november in 2019. Statistical software program was used to analysis the research data. For the purpose of study, arithmetic mean and standard deviation values were determined morever T-test and one-way variance analysis (ANOVA) test were applied to determine the differentiation status of the scores related to variables. In order to determinate the difference between the selected groups, Scheffe and LSD tested were applied. As a result of the research, according to ''athletic coping skills inventory'' the ability of athlete student to deal with sports problems was found in moderate level furthermore the levels of psychological attitude for sports differed significantly in terms of gender and grade variables. Lastly, in terms of parents educational status and family monthly income variables, there is no significant differences were detected.